Nanotechnology Meets Immunotherapy: CAR-T Cells Technology and Beyond - Loris, Rizzello (Journal of Biomaterials, 2018)
The crusade against cancer has a new army: immunotherapy. The rational design is very simple, but brilliant at the same time. Extract the patients T-cells, reprogram them in vitro for the expression of highly specific receptors against cancer, perfuse them back to the patient. As a result, T-cells are now instructed to selectively kill circulating tumor cells, while avoiding potential side effects. This ‘Fairy Tale’ however does not lack of drawbacks and limitations. First, malignant progression can be accompanied by profound immune suppression, which counteracts the immune system-mediated tumor elimination. Second, the immune cells modification does not match high standards in terms of safety for humans. Here, nanotech can fill these gaps, and help immunotherapy to be safer and more effective.